P134 Once daily fibrinolytic therapy in the management of pleural infection. (11th November 2022) - Virk, HS; Tsaknis, G; Naeem, M; Reddy, R
Abstract : Introduction and Objectives: The use of intrapleural fibrinolytic therapy in patients with pleural infection has been shown to reduce hospital stay and reduce surgical referral rate. However, the logistics and cost of delivering twice-daily dosing may have contributed to its underutilisation. Trials are ongoing to establish the most appropriate dosing regime. We explored the feasibility and outcomes of an alternative, reduced cost, once-daily dosing strategy. Methods: We completed a prospective observational study of concurrent dosing with once-daily Alteplase and DNase (Deoxyribonuclease) in adult patients with pleural infection, in a single district general hospital. Patients with iatrogenic infections, pregnancy, life expectancy <3 months and those with a known sensitivity to Alteplase or DNase were excluded. Patients with evidence of pleural infection (pleural fluid pH<7.2, gram stain positive for organisms, or bacterial growth in patients with clinic evidence of infection) were evaluated by bedside thoracic ultrasound. Patients with septations/multiloculated effusions received once-daily intrapleural 10 mg Alteplase and 5 mg DNase for a maximum of 3 days. The primary outcome was need for surgical referral, and the secondary outcomes included mortality at 3 months, length of hospital stay, duration of antibiotic therapy and percentage of predicted FVC at 4 months. Results: 46 consecutive patients diagnosed with pleural infection were included. Of those, 26 received at least one dose of fibrinolytic therapy via chest tube, 14 received intercostal tube drainage and 6 received aspiration alone. 2 patients, both of whom received fibrinolytics, were referred for surgery, but for indications other than management of pleural infection (lung cancer n=1, persistent pneumothorax n=1). 2 patients died within 3 months of diagnosis- one from aspiration pneumonia and one from post surgical complications. The mortality was similar to what was expected based on the RAPID mortality prediction score for the patients in the cohort. Table 1 also summarises other outcomes. Conclusions: This study shows that a cheaper and less onerous once-daily fibrinolytic regime is feasible and achieved acceptable outcomes similar to those expected from standard regimes. Further studies are needed to confirm this.